Перспективи застосування електромагнітного транспорту - Скосар, В.Ю.; Бурилов, С.В.; Дзензерський, В.О. (Доповіді НАН України, 2025)
Розглянуто технічні характеристики електромагнітного транспорту, зокрема, електромобілів, високошвидкісних магнітолевітаційних потягів, надвисокошвидкісних магнітолевітаційних потягів у вакуумованому трубопроводі, рейкотронів. Наведено технічні характеристики акумуляторних батарей, які використовуються як джерела живлення для електромобілів. Проаналізовано перспективи розвитку електромагнітного транспорту. The technical characteristics of electromagnetic transport, in particular, electric vehicles, high-speed maglev trains, ultra-high-speed maglev trains in vacuum pipeline, and railguns are considered. The technical characteristics of rechargeable batteries used as power sources for electric vehicles are presented. The prospects for the development of electromagnetic transport are analyzed. It has been concluded that electromagnetic transport systems have good, albeit limited, prospects for further development and use. Electric vehicles have very good prospects for further development, provided that the technical and environmental characteristics of batteries and fuel cells are improved and their cost is reduced. But there are also problems: no economically efficient and effective technology has yet been developed for recycling used lithium batteries and recovering secondary lithium and other valuable metals. The prospects for Maglev trains are limited, but could improve significantly if scientific and technical breakthroughs occur in the field of high-temperature superconductivity, which will lead to new technical solutions and a reduction in the cost of this transport. The development of commercial Maglev transport is being carried out through the construction of urban non-high-speed routes. The construction of new high-speed routes continues at a slow pace. Given the technical difficulties and unresolved safety issues, the prospects for ultra-high-speed vacuum transport are even more limited. Given the technical complexity, railguns will continue to be used in scientific and technical field and in space technology to test the strength of space materials. To significantly increase the efficiency of railguns, breakthroughs are needed in the field of new materials for rails and macroteils, which would reduce material removal from the surface under extreme operating conditions.